Plastitar records in marine coastal environments worldwide from 1973 to 2023 - Ellrich, Julius A.; Ehlers, Sonja M.; Furukuma, Shunji (Frontiers in Marine Science, 2023)
Plastics embedded in tar residues encrusting rocky coastlines were discovered on the Canary Islands (NE Atlantic Ocean) and termed “plastitar” in 2022. As plastic and tar pollution is widespread in marine pelagic and benthic habitats, it was predicted that this novel plastic form could occur on other coasts as well. To test this prediction, we reviewed the literature on plastic embedded in tar and examined rocky coastlines in our regions for plastitar. We found eight studies which reported plastic embedded in tar under several descriptions and terms (including “tar-bonded beach-conglomerate tarcrete”, “plasto-tar crust”, “plasto-tarball” and “plastitar”) in India (Arabian Sea), Bermuda (Saragossa Sea), the Bahamas (NW Atlantic Ocean), the United Arabic Emirates (Arabian Gulf and Gulf of Oman), Malta (central Mediterranean Sea), Croatia (Adriatic Sea), Italy (Adriatic and Ligurian Sea), Cabrera island, Menorca island and Sardinia island (western Mediterranean Sea) and Indonesia (Java Sea) from 1973 to 2023. We also detected plastitar during our field surveys in Japan (Sea of Japan) and Mallorca island (western Mediterranean Sea) in 2022 and 2023, respectively. Using Fourier-transform infrared spectroscopy (FTIR), we verified the contained plastics as polyethylene (PE). Pyrolysis-gas chromatography-mass spectrometry (PY-GC/MS) indicated that the tar residues derived from crude oil. Furthermore, plotting all these plastitar records in a global map revealed that almost all plastitar findings were made along the major oil transportation routes across the northern hemisphere suggesting that plastitar resulted from tanker-released crude oils. Overall, our study shows, for the first time, that plastitar has been a widespread and long overlooked plastic form in coastal systems worldwide.